2007
DOI: 10.1111/j.1467-8624.2007.01016.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental Sensitivity and Attachment in Children With Autism Spectrum Disorder: Comparison With Children With Mental Retardation, With Language Delays, and With Typical Development

Abstract: This study on sensitivity and attachment included 55 toddlers and their parents. Samples included children with autism spectrum disorder (ASD), mental retardation, language delay, and typical development. Children were diagnosed at 4 years of age. Two years before diagnosis, attachment was assessed with the Strange Situation procedure, and parental sensitivity and child involvement during free play were assessed with the Emotional Availability Scale. Parents of children with ASD were equally sensitive as paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
130
3
16

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 200 publications
(158 citation statements)
references
References 47 publications
9
130
3
16
Order By: Relevance
“…These findings were subsequently replicated in a toddler sample by Naber et al (2007a). These findings suggest that when autistic stereotypies are excluded from consideration, the disorganized attachment classification can nonetheless be assigned for children with autism, with expectable correlates (see also Koren-Karie et al, 2009; Van IJzendoorn et al, 2007). …”
Section: Attachment Organization In Autismmentioning
confidence: 97%
See 4 more Smart Citations
“…These findings were subsequently replicated in a toddler sample by Naber et al (2007a). These findings suggest that when autistic stereotypies are excluded from consideration, the disorganized attachment classification can nonetheless be assigned for children with autism, with expectable correlates (see also Koren-Karie et al, 2009; Van IJzendoorn et al, 2007). …”
Section: Attachment Organization In Autismmentioning
confidence: 97%
“…Studies using the Ainsworth Strange Situation procedure (Ainsworth & Wittig, 1969) find that 40–60% of preschool-age children with autism are classified as securely attached, based on Mary Ainsworth’s original secure/avoidant/resistant classification system (Capps et al, 1994; Koren-Karie et al, 2009; Shapiro et al, 1987; Van IJzendoorn et al, 2007; Willemsen-Swinkles et al, 2000). In the first Strange Situation study conducted with toddlers, Naber et al (2007a) found that 35% of toddlers with a diagnosis of Autistic Disorder and 43% of toddlers with a diagnosis of Pervasive Developmental Disorder Not Otherwise Specified (PDD-NOS) were classified as securely attached (see also Naber et al, 2008).…”
Section: Attachment Organization In Autismmentioning
confidence: 99%
See 3 more Smart Citations